Monitoring the Level of Antibiotic Purchase without a Prescription among Libyan Young Adults - Atia, Ahmed (Indian Journal of Pharmacy Practice)
Antibiotics are typically prescription only medicines. A high percentage of world’s antibiotics are sold without prescription by health-care specialists. The study assessed use of antibiotics without prescription among young adults in Libya. A pre-tested questionnaire was designed to evaluate reported name and utilization of antibiotics without prescription. Of 610 participants approached, 582 decided to contribute in this study, giving a response rate of 95.4%. 56.19% respondents conveyed acquisition of an antibiotic without a prescription. Only 21.1% correctly named an antibiotic as the medicine obtained. Among the survey participants who utilized an antibiotic without a prescription, 98.1% used antibiotic for insufficient period (< 3 days) or at inappropriate dosing intervals. The most frequently named antibiotic bought without a prescription is Augmentin®. An attention of health care policy makers should be focused on physicians and pharmacists, as the main information providers of rational antibiotic use, as well as on community pharmacies, identified as the main source of non-prescription antibiotics.
Keywords: Antibiotics; Self-medication; Prescription; Young Adult; Libya.